2023
DOI: 10.1161/str.54.suppl_1.wp56
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WP56: Improvement In Motor And Language Domains Mediates Most Of The Effect Of 24h NIHSS Improvement On Functional Independence

Abstract: Introduction: Improvement in NIH stroke scale scores on 24h follow-up is considered a key prognostic element after endovascular thrombectomy (EVT). We aimed to evaluate the proportion of effect of 24h NIHSS improvement on mRS 0-2 at 90d mediated through improvement in motor and language domains. Methods: From SELECT study, EVT patients with detailed NIHSS components on presentation and 24h follow-up as well as complete mRS on discharge and 90d were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Currently, 4 RCTs have been published to compare the outcomes of EVT vs medical management in patients with large infarct. [3][4][5][6] The RESCUE-Japan LIMIT trial 5 was the first RCT conducted in Japan to demonstrate that in patients with large infarct, stroke defined as an ASPECTS score of 3 to 5 (assessed by MRI mostly) with symptom onset within 6 hours or between 6 and 24 hours, and no signal change on MR-fluidattenuated inversion recovery, EVT led to better functional outcomes but increased the risk of ICH. The SELECT2 trial 4 was an international RCT enrolling patients with anterior circulation LVO with ASPECTS of 3 to 5 on NCCT or infarct core volume greater than 50 mL and demonstrated that EVT resulted in better functional outcomes than medical management, with an increased risk of vascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, 4 RCTs have been published to compare the outcomes of EVT vs medical management in patients with large infarct. [3][4][5][6] The RESCUE-Japan LIMIT trial 5 was the first RCT conducted in Japan to demonstrate that in patients with large infarct, stroke defined as an ASPECTS score of 3 to 5 (assessed by MRI mostly) with symptom onset within 6 hours or between 6 and 24 hours, and no signal change on MR-fluidattenuated inversion recovery, EVT led to better functional outcomes but increased the risk of ICH. The SELECT2 trial 4 was an international RCT enrolling patients with anterior circulation LVO with ASPECTS of 3 to 5 on NCCT or infarct core volume greater than 50 mL and demonstrated that EVT resulted in better functional outcomes than medical management, with an increased risk of vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] The RESCUE-Japan LIMIT trial 5 was the first RCT conducted in Japan to demonstrate that in patients with large infarct, stroke defined as an ASPECTS score of 3 to 5 (assessed by MRI mostly) with symptom onset within 6 hours or between 6 and 24 hours, and no signal change on MR-fluidattenuated inversion recovery, EVT led to better functional outcomes but increased the risk of ICH. The SELECT2 trial 4 was an international RCT enrolling patients with anterior circulation LVO with ASPECTS of 3 to 5 on NCCT or infarct core volume greater than 50 mL and demonstrated that EVT resulted in better functional outcomes than medical management, with an increased risk of vascular complications. The ANGEL-ASPECT RCT 3 involving Chinese patients with anterior circulation LVO who had ASPECTS of 3 to 5 on NCCT within 24 hours after symptom onset or ASPECTS of 0 to 2 on NCCT with in-farct core volume of 70 to 100 mL within 24 hours after symptom onset also found that EVT was associated with better clinical outcomes compared with medical management for such patients, with a higher ICH rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations